Implications of Court Versus Conference: The Relationship Between Perceptions of Procedural Justice and Shame Management. (March 2015) - Scheuerman, Heather L.; Keith, Shelley
Courts and conferences emphasize varying elements of procedural justice to ensure that outcomes are fair and invoke moral regret or shame among offenders. How procedural justice relates to the various ways shame is experienced or managed is, however, not clear. Using data from the Australian Reintegrative Shaming Experiments (RISE), we examine how four types of shame management—shame acknowledgment, shame displacement, shame avoidance, and internalizing shame—operate within the context of traditional court processing and the restorative justice conference. Results indicate that the type of treatment offenders receive (court vs. conference) and perceptions of procedural justice affect shame management, highlighting important implications for understanding how shame management influences recidivism within court and conference.